Three-dimensional finite element analysis for best angles of dog canine teeth implantation - Zhou, Ziyao; Zhang, Huimin; Ren, Yuxin; Zhou, Xiaoxiao; Liu, Haifeng; Zhong, Zhijun; Peng, Guangneng; Cheng, Jianguo; Zheng, Chengli (The Thai Journal of Veterinary Medicine, 2023)
Dental implantation is a tendency treatment for teeth lesions in small animal medicine. Canine teeth damage is the most common clinical injury for small animals. The aim of this study is to investigate appropriate angles for clinical canine teeth implantation. In this study, we built a simple mandibular model according to the measured oral indexes of five beagle dogs. Three-dimensional finite element analysis for the comparisons of different canine dental implant angles (30 °-80 °) in a local bone block model were performed. The maximum equivalent elastic strain and the maximum equivalent stress for different planting angles were next compared. As for the results, the peak equivalent stress of the implant ranges was from 132.11 to 277.81 MPa between 30 °- 80 °, with the peak equivalent strain from 774.96 to 1676.50 bone strain, under the average bite force (256 N). 66 ° is the best angle for dog canine dental implantation, with a 132.11 MPa of peak equivalent stress and 744.96 peak bone strain under 256 N bite force. The acceptable angle range of oblique implantation of dog canines can be 47 °- 80 ° (200-1000 bone strains). However, for a maximum bite force (1394 N), any implantation may contribute pathological changes for alveolar bone (greater than 3000 bone strain). Our study provides a reference for appropriate clinical canine teeth implantation.